PATTERNS OF TIES BETWEEN THICKNESS AND SPREADING OF TERRIGENOUS SEDIMENTS ON THE EXAMPLE OF UKRAINIAN SHIELD IN THE NORTH - Baran, A. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
This article focuses on identifying patterns typical for formations of sediment stratum that covers crystalline foundation in the north of Ukrainian shield, and on their basisfinding new methods that could be used during regional research, and also while exploring and prospecting sediment minerals fields. In particular, there are researches of statistical relations between average thickness and spreading of terrigenous sediments using the example of two territories situated on Novograd block of Volyn mega block and Fastiv block of Rosynsk-Tikytsk mega block. For this purpose, method of double correlation analysis was used. It was found out that there are various correlation connections between these indexes for the whole stratum, Quaternary and Neogene deposits. Part of them has strong and very strong relative connections. The following pattern was identified: in relatively well sorted or not sorted sediments correlational connection between thickness and spreading is always stronger than in all the sediments together in the case when they form the bigger part of sediment stratum volume or the volume of its researched part. Thus, one of the main factors that influence the correlational connections between thickness and spreading of all the sediment stratum or its part is their sorted or unsorted state. The information about existence of strong correlation connections between thickness and spreading of sediments of all the sediment stratum or its part can makegeological or sedimentological maps more substantial if they reflect spreading of these sediments. In this case according to the region of spreading of a sediment one can make at least qualitative evaluation of its average thickness, and thus its volume on the territory that is shown on the map. The identified pattern can be used while calculating projected resources of some minerals in some fields, zones, areas of their spreading. First of all, it concerns minerals that form separate horizons. They are secondary kaolin, expanded and bentonite clay, brown coal etc. With the help of this pattern one can calculate mineragenic potential in separate topographical sheets, administrative and geomorphological areas etc. The research of correlation connections between sediment thickness and spreading on the other mega blocks of Ukrainian shield and other regions may be perspective.
Keywords: sediments; thickness; spreading; correlation; resources; minerals; shield